The use of informing speech act as advertising strategy - Laila Sarah (Jurnal Linguistik Terapan, 2015)
Facebook is one of social media ranked as the fifth most accessed website in Indonesia. There is a way of using Facebook as a marketing means which is creating groups designed exclusively for selling products. This article discusses advertisement taken from Malang culinary group in Facebook called ‘Malang Kuliner’. The researcher focuses on the direct informing speech act (in other words, ‘pure’ informing) found in the study. Although there are indirect speech acts found in the data, the researcher does not address them. The research design of this study uses a case study. It is a document analysis employing qualitative approach. The result shows that the direct speech act of informing is the most used by the popular vendors in ‘Malang Kuliner’ (43.7% from 293 utterances). According to this study, a successful advertisement is not always about telling people to buy the product or making promises related to the product. In some cases, giving ‘pure’ information can actually be the most preferable strategy chosen by the advertisers to achieve their marketing goal in online advertisement.